Investigating the association between polyunsaturated fatty acids and osteomyelitis by Mendelian randomization - Baixing Chen; Bin Pu; Shi Lin; Shaoshuo Li; Hang Dong (Scientific Reports)
Abstract Osteomyelitis, characterized by bone inflammation and infection, poses a significant global health burden. This Mendelian randomization (MR) study investigates the causal relationship between polyunsaturated fatty acids (PUFAs) and osteomyelitis risk. By using GWAS data from 114,999 individuals, we explore specific PUFAs and their genetic variations using Inverse variance weighted (IVW), MR-Egger and weighted median methods. The results reveal a suggestive association between genetically predicted higher docosahexaenoic acid (DHA) and omega-6 levels with increased osteomyelitis risk. Conversely, a negative association is found for the omega-6:3 ratio. Linoleic acid, omega-3, and omega-6 show no significant associations. Heterogeneity and pleiotropy analyses support result robustness, indicating minimal confounding effects. Sensitivity analyses confirm the stability of findings. Our MR analysis challenges the presumed protective role of omega-3 in osteomyelitis, suggesting a nuanced relationship where DHA may pose an increased risk. The study underscores the complexity of fatty acid interactions influenced by genetic variability and dietary nuances. Further research is essential to unravel underlying mechanisms and translate these findings into actionable strategies for osteomyelitis prevention and treatment.